2022
DOI: 10.3390/molecules27185751
|View full text |Cite
|
Sign up to set email alerts
|

Aziridination Reactivity of a Manganese(II) Complex with a Bulky Chelating Bis(Alkoxide) Ligand

Abstract: Treatment of Mn(N(SiMe3)2)2(THF)2 with bulky chelating bis(alkoxide) ligand [1,1′:4′,1′′-terphenyl]-2,2′′-diylbis(diphenylmethanol) (H2[O-terphenyl-O]Ph) formed a seesaw manganese(II) complex Mn[O-terphenyl-O]Ph(THF)2, characterized by structural, spectroscopic, magnetic, and analytical methods. The reactivity of Mn[O-terphenyl-O]Ph(THF)2 with various nitrene precursors was investigated. No reaction was observed between Mn[O-terphenyl-O]Ph(THF)2 and aryl azides. In contrast, the treatment of Mn[O-terphenyl-O]P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 122 publications
1
2
0
Order By: Relevance
“…This quintet corresponds to high-spin Fe iii antiferromagnetically coupled to carbene radical anion. Significant ligand radical character is consistent with our earlier work on Co carbene, 27 Fe/Mn nitrenes, 21,29 and Fe azide/diazoester complexes in this ligand environment. 20,26 Upon addition of styrene, either directly or through attempted coordination to Fe, significant rearrangement of the carbene during geometry optimization resulted in one or both of the esters coordinated to Fe and the carbene uncoordinated.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This quintet corresponds to high-spin Fe iii antiferromagnetically coupled to carbene radical anion. Significant ligand radical character is consistent with our earlier work on Co carbene, 27 Fe/Mn nitrenes, 21,29 and Fe azide/diazoester complexes in this ligand environment. 20,26 Upon addition of styrene, either directly or through attempted coordination to Fe, significant rearrangement of the carbene during geometry optimization resulted in one or both of the esters coordinated to Fe and the carbene uncoordinated.…”
supporting
confidence: 90%
“…[16][17][18][19] We previously reported the synthesis and group-transfer reactivity of middle and late 3d metal complexes in weak-field bis(alkoxide) ligand environments. [20][21][22][23][24][25][26][27][28][29][30] The reaction of Co(OR) 2 (THF) 2 (OR¼OC t Bu 2 Ph) with diphenyldiazomethane formed high-valent, low-spin cobalt-carbene Co(OR) 2 (¼CPh 2 ) with an electronic structure intermediate between cobalt(IV)alkylidene and carbene(III)-carbene radical. 22 One-electron reduction of this compound produced high-spin Co(II) weakly coupled with a carbene radical.…”
mentioning
confidence: 99%
“…Fewer studies have examined weaker-field alkoxides as supporting ligands for late, first-row transition metals, primarily due to the propensity of alkoxides to form cluster compounds , if not carefully tuned. Nevertheless, several groups have made use of either fluorinated alkoxides to minimize the π-donicity of the ligand and thus inhibit clustering or sterically encumbering alkoxides to enable the formation of well-defined mononuclear complexes. , These investigations have revealed that alkoxide complexes can accommodate unique electronic configurations (e.g., high-spin square planar complexes , ) and indeed allow access to high-spin metal–ligand multiply bonded intermediates (e.g., an iron–oxo example as well as iron–imido complexes not directly detected, but proposed based on reactivity and computational support).…”
Section: Introductionmentioning
confidence: 99%